2016
DOI: 10.1002/nau.23179
|View full text |Cite
|
Sign up to set email alerts
|

No immediate effect on urodynamic parameters during transcutaneous electrical nerve stimulation (TENS) in children with overactive bladder and daytime incontinence-A randomized, double-blind, placebo-controlled study

Abstract: There is no immediate objective effect of TENS on bladder activity assessed by natural fill urodynamics in children with OAB and DUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Twenty-nine articles were excluded because they did not provide useful data, and 1 article was excluded because it described an experiment. Eight papers described RCTs [14][15][16][17][18][19][20][21] evaluating the effects of TENS treatment in children on urodynamic indexes and objective OAB symptoms. Details on the studies and characteristics of the patients are shown in Table 1.…”
Section: Study Selection Process Search Results and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-nine articles were excluded because they did not provide useful data, and 1 article was excluded because it described an experiment. Eight papers described RCTs [14][15][16][17][18][19][20][21] evaluating the effects of TENS treatment in children on urodynamic indexes and objective OAB symptoms. Details on the studies and characteristics of the patients are shown in Table 1.…”
Section: Study Selection Process Search Results and Characteristicsmentioning
confidence: 99%
“…All 8 of the studies included in our meta-analysis followed a randomization process. Five papers [14,15,18,19] had an appropriate calculation of the number of patients. Two studies [19,20] did not specify a blinding protocol, with a Jadad score of B (Table 2).…”
Section: Risk Of Bias In the Studiesmentioning
confidence: 99%
“…However, no differences were seen in maximal and average voided volumes or urodynamic data. 71 , 72 Another group studied the additional effect of parasacral stimulation in patients receiving urotherapy; 73 62 children with OAB were randomized either to urotherapy alone or combined with parasacral stimulation. In the standard group, 46% were completely dry versus 67% in the combined group; this was not significant.…”
Section: Resultsmentioning
confidence: 99%
“…10 Percutaneous tibial nerve stimulation (PTNS) and SNS have similar mechanisms of effect. [16][17][18] In the present study, TENS electrodes were placed bilaterally below and approximately 15-cm above the malleolus medialis to carry out TTNS. 10 The exact mechanism and neurological pathways underlying the improvements observed with PTNS and TTNS remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used TTNS for the treatment of urinary incontinence, active bladder, fecal incontinence and anal fissure. [16][17][18] In the present study, TENS electrodes were placed bilaterally below and approximately 15-cm above the malleolus medialis to carry out TTNS. This method achieved substantial improvement in the symptoms of geriatric patients with constipation.…”
Section: Discussionmentioning
confidence: 99%